KONSELING PADA LANJUT USIA: KAJIAN LITERATUR TENTANG PERMASALAHAN PSIKOLOGIS DAN PENDEKATAN INTERVENSI - Putri Hidayati; Amirah Diniaty (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to comprehensively examine the psychological problems faced by elderly individuals (lansia) and to identify evidence-based counseling approaches and techniques relevant to addressing those needs. The research employs a descriptive qualitative method using a library research design. Data were collected through a review of scientific documents comprising international and national journals, academic textbooks, and official reports from competent institutions published within the last ten years. Analysis was conducted using content analysis technique through three stages: data reduction, data presentation, and conclusion drawing. The findings indicate that elderly individuals face complex psychological challenges including depression, anxiety, loneliness, existential crisis, and cognitive decline impacts. Counseling approaches proven effective include life review therapy, reminiscence therapy, adapted cognitive-behavioral therapy (CBT), existential-humanistic counseling, and problem-solving therapy. In the Indonesian context, integration of Islamic values and local wisdom strengthens intervention effectiveness. The study recommends developing counselors' gerontological competencies and the formulation of inclusive counseling service policies for the elderly.